Endophytic Bacillus subtilis antagonize soil-borne fungal pathogens and suppress wilt complex disease in chickpea plants (Cicer arietinum L.) - Mageshwaran, Vellaichamy; Gupta, Rishabh; Singh, Shailendra; Sahu, Pramod K.; Singh, Udai B.; Chakdar, Hillol; Bagul, Samadhan Y.; Paul, Surinder; Singh, Harsh V. (Frontiers in Microbiology, 2022)
The present study aimed to identify potential endophytic bacteria antagonistic against three soil-borne fungal pathogens, Rhizoctonia solani, Sclerotium rolfsii, and Fusarium oxysporum f.sp. ciceri causing root rot, collar rot, and fungal wilt diseases in chickpea, respectively. A total of 255 bacterial endophytes were isolated from leaf, stem, and root of seven different crop plants (chickpea, tomato, wheat, berseem, mustard, potato, and green pea). The dual culture-based screening for antifungal property indicated that three endophytic isolates had strong inhibition (>50%) against all the three pathogens tested. Based on morphological, biochemical, and molecular characterization, the selected isolates (TRO4, CLO5, and PLO3) were identified as different strains of Bacillus subtilis. The bacterial endophytes (TRO4 and CLO5) were positive for plant growth promoting (PGP) traits viz., ammonia, siderophore, and indole-3-acetic acid (IAA) production. Bio-efficacy of the endophytes (TRO4, CLO5, and PLO3) was tested by in planta trial in chickpea pre-challenged with R. solani, S. rolfsii, and F. oxysporum f.sp. ciceri. B. subtilis strains TRO4 and CLO5 were found to be effective in reducing percent disease incidence (p≤0.05) and enhancing plant growth parameters. The different root parameters viz. root length (mm), surface area (cm2), root diameter (mm), and root volume (cm3) were significantly (p≤0.05) increased in TRO4 and CLO5 inoculated chickpea plants. Confocal Scanning Laser Microscopy showed heavy colonization of bacteria in roots of endophyte inoculated chickpea plants. The inoculation of endophytic Bacillus subtilis strains TRO4 and CLO5 in chickpea through seed biopriming reduced the accumulation of superoxide, enhanced the plant defence enzymes, and induced the expression of Pathogenesis-Related (PR) genes. Semi-quantitative analysis of defense related genes showed differential activation of PR genes (60srp and IFR) by endophyte inoculation. Results of the present study revealed antagonistic potential of B. subtilis strains TRO4 and CLO5 against three major soil-borne fungal pathogens and its ability to suppress wilt complex disease in chickpea. This is the first report on simultaneous suppression of three major soil borne fungal pathogens causing wilt complex in chickpea by endophytic B. subtilis strains.